Global Implications of Lower Oil Prices - Husain, Aasim; Arezki, Rabah; Breuer, Peter; Haksar, Vikram (Washington, D.C. : International Monetary Fund, 2015)
The sharp drop in oil prices is one of the most important global economic developments over the past year. The SDN finds that (i) supply factors have played a somewhat larger role than demand factors in driving the oil price drop, (ii) a substantial part of the price decline is expected to persist into the medium term, although there is large uncertainty, (iii) lower oil prices will support global growth, (iv) the sharp oil price drop could still trigger financial strains, and (v) policy responses should depend on the terms-of-trade impact, fiscal and external vulnerabilities, and domestic cyclical position.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet